Investments - Bodie, Zvi; Kane, Alex, 1942-; Marcus, Alan J. (The McGraw-Hill Education series in finance, insurance, and real state, 2021)
"Investments, Twelfth Edition, is intended primarily as a textbook for courses in investment analysis. Our guiding principle has been to present the material in a framework that is organized by a central core of consistent fundamental principles. We attempt to strip away unnecessary mathematical and technical detail, and we have concentrated on providing the intuition that may guide students and practitioners as they confront new ideas and challenges in their professional lives."--Provided by publisher.